The influence of local revenue, balancing funds and private investment on economic growth and welfare of communities in East Java Province - Dudy Firmansyah (Institute of Advanced Scientific Research, Inc., 2019)
This study aims to analyze influence of local revenue (PAD), general allocation fund (DAU), special allocation fund (DAK), sharing fund (DBH), and private investment on economic growth, and influence of economic growth towards public welfare in East Java Province. The study was done usingquantitative approach. The study population were 38 regencies and cities in East Java. The analysis was done using E-views software and the technique used was panel regression analysis. The key findings of this work has shown that local revenue had positive effect on economic growth in regencies and cities in East Java Province with significance value of 0.0102. In addition, results showed that general allocation fund had positive influencedon economic growth with significance value of 0.000. On the other hand, result showed that special allocation fund had negative influence on economic growth. Result showed that private investment had positive influence toward economic growth. Thus overall, it is concluded that PAD, DAU, DAK and private investment had influenced on economic growth, while DBH did not exhibit any influence on the economy. Â© 2019, Institute of Advanced Scientific Research, Inc.. All rights reserved.